American Odyssey: A Ghost Rifle Western - McCoy, Max (Thorndike, Maine : Center Point Large Print, 2022)
"Ten years have passed since Jack Picaro lost his Ghost Rifle--the firearm he invented, the one that never missed its target. The loss of the rifle calmed the hellraiser in his soul. Instead of returning to the gambling halls and whiskey bars of St. Louis, Jack has spent the last decade as a fur trapper in Wyomings Wild River Range, married to Sky, the daughter of an Arikara war chief, and father of two. Then, after helping rescue U.S. soldiers trapped on a dangerous snow-covered trail in the Rocky Mountains, Jack hears the familiar bell-like report of his Ghost Rifle. Determined to retrieve his deadly property, he travels deep into Lakota territory, facing down old enemies--and resuming old sinful habits--unaware of what awaits him when he eventually returns home to his family. And unaware of a man pursuing him from St. Louis--a man Jack has never met, but who has a personal score to settle . . ."--
Keywords: Frontier and pioneer life -- Fiction; Rifles -- Fiction; Indians of North America -- Fiction; Gunsmiths -- Fiction; Fur trade -- Fiction; West (U.S.) -- Fiction; Western fiction